2020
DOI: 10.3390/foods9070854
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Inflammatory and Atheroprotective Properties of Wheat Gluten Protein Hydrolysates in Primary Human Monocytes

Abstract: Bioactive protein hydrolysates have been identified in several sources as possible agents in the prevention and treatment of many diseases. A wheat gluten (WG) concentrate was hydrolyzed by Alcalase under specific conditions. The resulting hydrolysates were evaluated by in vitro cell-free experiments leading to the identification of one bioactive WG protein hydrolysate (WGPH), which was used at 50 and 100 μg/mL on primary human monocytes. Reactive oxygen species (ROS) and nitrite levels and RT-qPCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…The chemical composition of KPHs was similar to KPI. These results are similar to those obtained in other pseudocereals of emerging crops as wheat and higher than others as quinoa [ 38 ]. The main difference between KPI and KPHs was higher ash content in the hydrolysates because of the addition of alkali to maintain the pH constant during hydrolysis.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The chemical composition of KPHs was similar to KPI. These results are similar to those obtained in other pseudocereals of emerging crops as wheat and higher than others as quinoa [ 38 ]. The main difference between KPI and KPHs was higher ash content in the hydrolysates because of the addition of alkali to maintain the pH constant during hydrolysis.…”
Section: Resultssupporting
confidence: 90%
“…The relation tween the hydrolysates MWs and their bioactivities in human health applicatio sential in functional foods. It has been demonstrated that the presence of low-M tides enhances the absorption and the ability of amino acids to have bioactive eff The MW average of kiwicha peptides is lower than MW average of other pseud peptides as wheat gluten protein hydrolysates, which after hydrolysis with demonstrated to be constituted by peptides with sizes in the range of 1-300 kDa three of 30.08, 5.36, and 2.19 kDa [38]. In this sense, the smaller size of kiwicha may be attributed to faster hydrolysis with Bioprotease compared to Alcalase.…”
Section: Analysis Of the Hydrolysis Degree And The Molecular Profile Of Kiwicha Protein Productsmentioning
confidence: 99%
“…With the exception of milk and egg components, in general, more studies with plant material have B A C D been carried out [14]. Our results of LPH decreasing the expression of pro-inflammatory cytokines are similar to others shown in plant-protein hydrolysates, such as wheat, gluten, or hemp [45,46].…”
Section: Effect Of Lph On Mrna Expression Of Pro-inflammatory Cytokinessupporting
confidence: 86%
“…Taken together with the demand for new foods, many research groups have led the development of plant and animal protein hydrolysis processes in a wide range of raw materials, such as fish [8], asparagus [9], hemp [6,10], meat byproduct [11] and wheat gluten protein [12], among others. However, there are few studies that show the potential techno-functional uses of chia seed in the food industry and its application as a food ingredient containing peptides with biological activity.…”
Section: Introductionmentioning
confidence: 99%